Depression, anxiety and insomnia in Chinese older adults and their family caregivers during the COVID-19 pandemic: an actor-partner interdependence model approach - Ding, Kai-Rong; Xu, Wen-Qi; He, Yong-Yi; Hu, Jia-Hui; Tan, Wen-Yan; Liao, Jing; Hou, Cai-Lan; Jia, Fu-Jun; Wang, Shi-Bin (Frontiers in Public Health, 2023)
Aims This study aimed to explore the dyadic effects of depression and anxiety on insomnia symptoms in Chinese older adults and their caregivers living in a community setting. Methods Data were collected from 1,507 pairs of older adults and their caregivers who were in the Guangdong Mental Health Survey in China. The 9-item Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder module 7 (GAD-7), and Insomnia Severity Index (ISI) were used to measure depression, anxiety, and insomnia symptoms. Actor-Partner Interdependence Models (APIM) were used to determine whether anxiety or depression symptoms predicted individual or dyadic insomnia. Results Older adults' and caregivers' depression and anxiety had significant positive correlations with their own and their caregivers' insomnia symptoms (all P < 0.001). Actor effects were found between depression and insomnia symptoms in both older adults and caregivers (B = 0.695, P < 0.001; B = 0.547, P < 0.001, respectively), with one significant partner effects (B = 0.080, P = 0.007). Actor effects were also found between anxiety and insomnia symptoms in both older adults and caregivers (B = 0.825, P < 0.001; B = 0.751, P < 0.001, respectively), with one significant partner effects (B = 0.097, P = 0.004). However, the caregivers' depression and anxiety were not associated with older adults' insomnia symptoms in the APIM analyses. Conclusions Older adults and their caregivers had an interrelationship between psychological distress and insomnia. Consequently, healthcare providers might consider involving dyads when designing programs to reduce insomnia and improve psychological distress for family caregivers.